PROSPECTS OF INTRODUCTION OF RESOURCE-SAVING METHODS OF PAULOWNIA GROWING TECHNOLOGY IN HILLY LANDS OF NAVOI REGION (CAHIERS MAGELLANES-NS, 2024)
In recent years, there has been a tradition of worldwide attention to improving the environmental situation and an ever-increasing demand for building materials and alternative biofuels. Harmonizing both of these situations, that is, the process of technological development and nature protection, improving the ecosystem, focusing on renewable biofuels is the content of this article.